Prevalence and determinants of oral health conditions and treatment needs among slum and non-slum urban residents: Evidence from Nigeria. - Mary E Osuh; Gbemisola A Oke; Richard J Lilford; Eme Owoaje; Bronwyn Harris; Olalekan John Taiwo; Godwin Yeboah; Taiwo Abiona; Samuel I Watson; Karla Hemming; Laura Quinn; Yen-Fu Chen (PLOS Global Public Health, 2022)
Oral diseases constitute a neglected epidemic in Low and Middle-Income Countries (LMICs). An understanding of its distribution and severity in different settings can aid the planning of preventive and therapeutic services. This study assessed the oral health conditions, risk factors, and treatment needs among adult residents in the slum and compared findings with non-slum urban residents in Ibadan, Nigeria. The Multistage sampling was used to select adult (≥18-years) residents from a slum and a non-slum urban sites. Information sought from participants included dietary habits, oral hygiene practices, and the use of dental services. Oral examinations were performed in line with WHO guidelines. Associations were examined using logistic regression. Mediation analysis was undertaken using generalized structural equation modeling. The sample comprised 678 slum and 679 non-slum residents. Median age in slum vs non-slum was 45 (IQR:32-50) versus 38 (IQR:29-50) years. Male: female ratio was 1:2 in both sites. Prevalence of oral diseases (slum vs non-slum sites): dental caries (27% vs 23%), gingival bleeding (75% vs 53%) and periodontal pocket (23% vs 16%). The odds of having dental caries were 21% higher for the slum dwellers compared to non-slum residents (OR = 1.21, 95% CI:0.94 to 1.56); and 50% higher for periodontal pocket (OR = 1.50, 95%CI: 1.13 to 1.98), after adjusting for age and sex. There was little evidence that tooth cleaning frequency mediated the relationship between place of residence and caries (OR = 0.95, 95%CI: 0.87 to 1.03 [indirect effect], 38% mediated) or periodontal pocket (OR = 0.95, 95%CI: 0.86 to 1.04, 15% mediated). Thirty-five percent and 27% of residents in the slum and non-slum sites respectively required the "prompt and urgent" levels of treatment need. Oral diseases prevalence in both settings are high and the prevalence was generally higher in the slum with correspondingly higher levels of prompt and urgent treatment needs. Participants may benefit from targeted therapeutic and health promotion intervention services.